Urgensi Pemenuhan Hak-Hak Konstitusional Warga Negara Era Pandemi Covid-19 di Indonesia - Supriyono Supriyono; Vavirotus Sholichah; Anang Dony Irawan (Penerbit Goodwood, 2022)
Purpose: This study aims to determine the constitutional rights of citizens that need to be protected and fulfilled by the state. And to know the rules related to the protection and fulfillment of the constitutional rights of citizens during the Covid-19 pandemic. Method: The research methodology used in this research is normative juridical by statute approach and conceptual approach. Results: This research resulted in an explanation of the fulfillment of the constitutional rights of citizens during the Covid-19 pandemic. The most crucial constitutional rights of citizens to be fulfilled are health rights, economic rights, and education rights. The non-fulfillment of the safety and constitutional rights of citizens is a form of denial of the mandate of the 1945 Constitution of the Republic of Indonesia. Limitation: The scope of the research is limited to fulfilling the constitutional rights of citizens during the Covid-19 pandemic. Contribution: The authors hope in the future, it is hoped that a more in-depth study can be carried out on research on the constitutional rights of citizens, especially in emergency conditions such as the Covid-19 pandemic.